2012
DOI: 10.1002/marc.201200695
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Responsive Conjugated Polymers to 1.5 μm and Beyond: Synthesis and Electrochromic Switching Application

Abstract: Azulene-containing conjugated polymers with near-infrared absorption up to 1.5 μm and beyond are achieved by treating with trifluoroacetic acid (TFA). Density functional theory calculations reveal that the near-infrared absorption arises from a strong intramolecular charge transfer transition on the polymer backbone, and the near-infrared absorption can be tuned by the degree of protonation. Furthermore, TFA treated polymers show a ten-fold enhancement in electrochromic contrast and significantly improved swit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…[3][4][5] Similarly, the physical, electronic, and optical properties of some natural pigments could offer access to key building blocks for developing bio-derived chromophoric materials. [9][10][11][12][13][14][15][16] Chemically, guaiazulene is a nonalternant hydrocarbon that is notable for its low transition energy to the S 1 state and unusually large S 1 -S 2 gap, [17][18][19][20][21][22][23][24][25][26][27] where S 1 and S 2 refer to the first and second electronically excited states, respectively. 3,8 Among known natural pigments, 6-8 guaiazulene has received recent popularity for its interesting physical and electronic properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] Similarly, the physical, electronic, and optical properties of some natural pigments could offer access to key building blocks for developing bio-derived chromophoric materials. [9][10][11][12][13][14][15][16] Chemically, guaiazulene is a nonalternant hydrocarbon that is notable for its low transition energy to the S 1 state and unusually large S 1 -S 2 gap, [17][18][19][20][21][22][23][24][25][26][27] where S 1 and S 2 refer to the first and second electronically excited states, respectively. 3,8 Among known natural pigments, 6-8 guaiazulene has received recent popularity for its interesting physical and electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…6-8 Additionally, the non-toxic nature and the accompanying eco-friendly feature of natural dyes could set the stage for chemists to develop "green" routes towards photonic and conductive materials. [17][18][19][20][21][22][23][24][25][26][27] It was shown that extending the conjugation through the seven-membered ring of the parent azulene with aromatic substituents dramatically impacts the optical, electrochemical, and electrochromic properties of the azulenylium carbocation. [9][10][11][12][13][14][15][16][17] As a nontoxic natural product found in the oils of Guajacum officinale and Matricaria chamomilla, as well as in the vibrant-blue mushroom Lactarius indigo, guaiazulene has been approved by the FDA as a cosmetic color additive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…135 Wang et al reported azulene-thiophene based CPs that exhibit electrochromism in near IR region (~1500 nm). 136 Azulene can be regarded as an aromatic 6π electron tropylium cation fused by a 6π electron cyclopentadienyl anion. Due to the electron-rich cyclopentadienyl anion, azulene can easily undergo electrophilic substitution at C-1 or C-3 in the 5membered ring and form a very stable aromatic 6π-electron azulenium cation (tropylium cation).…”
Section: Carbazole-based Conjugated Polymersmentioning
confidence: 99%
“…It is also popularly used in the syntheses of conjugated polymers for EC applications in the recent years. 119,120,135,136,172 Stille coupling, which is another…”
Section: Synthesis Of Conjugated Polymers Via Suzuki Couplingmentioning
confidence: 99%